Parents of children with cancer require health literacy support to meet their information needs - Tan, Chai Eng; Lau, Sie Chong Doris; Abdul Latiff, Zarina; Lee, Chee Chan; Teh, Kok Hoi; Mohd Sidik, Sherina (Wiley-Blackwell Publishing, 2023)
Background: Timely and relevant information helps parents to cope when a child is diagnosed with cancer. However, obtaining and understanding information is not a straightforward process for parents. Objectives: This article aims to explain paediatric cancer parents' information behaviour related to the care of their child. Methods: Qualitative in-depth interviews were conducted with fourteen Malaysian paediatric cancer parents and eight healthcare professionals who worked with paediatric cancer patients. Reflexivity and inductive approaches were used to interpret the data to identify meaningful themes and subthemes. Results: Three themes about how paediatric cancer parents interact with information emerged: Acquiring information, internalising information, and using information. Information may be actively sought or passively acquired. Cognitive and affective aspects influence how information is internalised into meaningful knowledge. Knowledge then leads to further action including further information gathering. Conclusion: Paediatric cancer parents need health literacy support to meet their information needs. They require guidance in identifying and appraising suitable information resources. Development of suitable supporting materials is needed to facilitate parents' ability to comprehend information related to their child's cancer. Understanding parents' information behaviour could assist healthcare professionals in providing information support in the context of paediatric cancer.